Wisdom in the process of humanizing culture : some Thomistic insights - Roszak, Piotr (Array, 2021)
In the light of Vatican II, the Christian contribution to contemporary culture can be characterized by the sapiential approach. Having determined the main obstacle or traps of the current cultural situation, as reported by B. Welte in terms of “unwesen”, this paper proposes the recovery of wisdom as the ultimate horizon of human activities. This approach can be developed in three ways, according to Aquinas’ characteristics of wisdom: enlargement of perspectives, ordering of the big picture and tasting which consists in restoring the distorted taste of things. Finally, possible conclusions for the Christian presence in the world are proposed.